Satisfaction Influence Use of Accounting Information Systems, Computer Anxiety, Technology Acceptance and Self-Efficacy Against Employee Performance PT. Delta Dunia Textile Sukoharjo - Yuli Chomsatu Samrotun, Dinda Elnusa Try Atmaja, Siti Nurlaela & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to determine the effect of satisfaction is the use ofAccounting Information Systems, Computer Anxiety, TechnologyAcceptance and Self-Efficacy against Employee Performance PT. DeltaDunia Textile Sukoharjo. This research was motivated by the importance ofthe application of information technology, the anxiety in using thetechnology, benefits and ease in operating the companys informationtechnology. With the quality and performance of employees both in themastery of information technology it will be a good contribution to thecompany, so as to compete competitively with other companies. This studyis located in one of the companies in Sukoharjo. Used a sample of 40respondents with sampling using purposive sampling technique. The resultsshowed; (1) There is no effect between satisfaction Usage AccountingInformation Systems on Employee Performance, (2) there is influencebetween Computer Anxiety on the Performance of Employees. (3) There isinfluence between the Technology Acceptance the Employee Performance,(4) There is influence between Self -Effivcacy the Employee performance.Keyword: Accounting information system; Computer Anxiety; TechnologyAcceptance; Self-efficacy; Employee performance